Crimean-Congo Hemorrhagic Fever Virus in Asia, Africa and Europe - Shahhosseini, Nariman; Wong, Gary; Babuadze, George; Camp, Jeremy V.; Ergonul, Onder; Kobinger, Gary P.; Chinikar, Sadegh; Nowotny, Norbert (Microorganisms (Basel), 2021)
The global spread of ticks and various tick-borne viruses (TBVs) suggests the possibility of new tick-borne diseases emerging. Crimean-Congo hemorrhagic fever virus (CCHFV) is an emerging TBV of the Nairoviridae family that causes serious disease that can be fatal in humans. CCHFV endemic foci can be found in Africa, Asia, the Middle East, and South-Eastern Europe, and has spread to previously unaffected regions and nations, such as Spain, over the last two decades. In this review, we discuss the current situation of CCHFV in Asia, Africa and Europe based on existing knowledge, and we discuss driving factors in the distribution and transmission of the virus, such as the spread of tick vector species and host reservoirs.